Voices of the past / Lisbeth Sinan Lendik Edmond - Lendik Edmond, Lisbeth Sinan (Universiti Teknologi MARA Cawangan Kedah, 2022)
A compilation of poems from interested 118 lecturers and academicians from UiTM and other higher learning institutions.